IMPACT OF FINANCIAL MARKET DEVELOPMENT ON GLOBAL COMPETITIVENESS AND FOREIGN DIRECT INVESTMENT - Batsyeba Sundari; Pradivta Alfatihah (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to test and analyze the impact of financial market development (FMD) on the global competitiveness index (GCI) and Foreign Direct Investment (FDI), case study in Indonesia during the 2007-2017 period. This study was analyzed by using linear regression to test the relationship or influence of the dependent variables and independent variables. This study employs a quantitative approach with secondary data obtained from global competitiveness report and Investment Coordinating Board website. The study revealed that eight indicators used to measure FMD were affected positive significant. The study also shows that FMD affects positive but insignificant on GCI and same results for GCI on FDI..